A Novel Study on the Maize Streak Virus Epidemic Model Using Caputo-Fabrizio Fractional Derivative (Contemporary Mathematics, 2023)
In this paper, we simulate a maize streak virus (MSV) epidemic model using the Caputo-Fabrizio fractional derivative. We solve a nonlinear fractional-order model of the MSV using a recently proposed efficient numerical method. We perform several graphical simulations to explore the proposed model dynamics. The proposed investigations justify the usefulness of the recently proposed scheme in epidemiology. The Caputo-Fabrizio type fractional-order generalization of the model and implementation of the method are the key features of this study.
Keywords: maize streak virus; fractional-order model; Caputo-Fabrizio derivative; numerical scheme; graphical simulations